Den Lernraum Betriebspraktikum gemeinsam öffnen Anspruch und Werkzeuge einer konnektivitätsorientierten Praktikumsdidaktik - Ostendorf , Annette (innsbruck university press, 2018)
"Mandatory internships have become a firmly anchored curricular element of many vocational medium and high schools. With the help of a connectivity-oriented internship didactics, the authors unfold a special perspective on the design of teaching / learning processes in experience-completing internships. The internship is understood as a conglomeration of learning places, activities and phases centered around learning and working in the internship. The opening up of this learning space requires both the commitment of the key actors of school and enterprise, as well as a juxtaposition of the actions described at a strategic and operational level in this book. A tool fund supports readers in implementing this connectivity-oriented perspective in their own professional context. Dr. Annette Ostendorf is a University Professor of Business Education and Head of the Institute for Organization and Learning at the University of Innsbruck. Dr. Bettina Dimai is a project assistant at the same institute and works as a freelance trainer and consultant. Mag. Christin Ehrlich, PhD and Mag. Hannes Hautz, MSc are scientific assistants at the Institute for Organization and Learning, Department of Business Education."